Optimalisasi Fungsi Perencanaan Kepala Ruangan pada Bedside Handover - Handayani, Eka; Wildani, Andi Amalia; Novieastari, Enie; Yatnikasari, Aat (Journal of Telenursing (JOTING), 2024)
This study aims to identify and analyze bedside handover problems using the role and function management approach. The research method used is a case study through analysis with a fishbone diagram, compiling innovations with Lewin's 3-step model approach. The results showed an increase in bedside handover compliance from 44% to 94.25%, the ineffectiveness of SBAR communication affected the observation results, verbally nurses understood the SOP for bedside handover, with the planning of the head of the room. In conclusion, there are obstacles and barriers to implementing this innovation such as the head of the room who also handles patients because there is an increase in patients and staff who are absent due to illness, CI / Katim / PPJA who handle patients with the same number as associate nurses so that the socialization and supervision process carried out in stages is not optimal. Keywords: Bedside Handover, Planning Function, Head of Room.